Empowering actors in transition management in and for cities. - Hölscher, Katharina; Avelino, Flor; Wittmayer, Julia M. (Springer, 2018)
The multi-actor nature of urban sustainability transitions challenges existing social fabrics and local governance settings, and raises questions about who takes decisions, with which agenda and to what end. It demands close attention to who are actors involved in transition processes and what are the implications for (changing) roles, responsibilities and relations of actors and networks. This chapter provides an overview of different understandings of actors and roles in transition management in and for cities and how actors are empowered through transition management interventions to advance urban sustainability transitions. We first review different approaches and heuristics to understand actors and roles in transition management and in relation to the underlying goal to influence urban sustainability transitions. These enable to analyse actors and (changing) roles, support the actor selection and enhance reflexivity in transition management processes. We then discuss what the notion of 'empowerment' captures in terms of how actors (re-)define, develop and enact roles and relationships in the pursuit of urban sustainability transitions as a result of transition management interventions in cities. We exemplify our reflections with insights from our empirical experiences with transition management processes.
Keywords: Nachhaltige Stadtentwicklung; Akteur; Netzwerk; Zivilgesellschaft; Transformation; Nachhaltigkeit; Stadtraum; Urban Governance